Impact of Point-of-Care Ultrasound in Medical Decision Making: Informing the Development of an Internal Medicine Global Health POCUS Curriculum - Michelle Fleshner; Steve Fox; Thomas Robertson; Ayako Wendy Fujita; Divya Bhamidipati (CINQUILL Medical Publishers Inc., 2022)
Background: Point-of-care Ultrasound (POCUS) is particularly useful in low-middle income countries (LMICs) where advanced imaging modalities and diagnostics are often unavailable. However, its use among Internal Medicine (IM) practitioners is limited and without standard curricula. This study describes POCUS scans performed by U.S. IM residents rotating in LMICs to provide recommendations for curriculum development.  Methods: IM residents within a global health track performed clinically-indicated POCUS scans at two sites. They logged their interpretations and whether or not the scan changed diagnosis or management. Scans were quality-assured by POCUS experts in the US to validate results. Using the criteria of prevalence, ease of learning, and impact, a framework was developed for a POCUS curriculum for IM practitioners within LMICs.  Results: A total of 256 studies were included in analysis. 237 (92.5%) answered the clinical question, 107 (41.8%) changed the diagnosis, and 106 (41.4%) changed management. The most frequently used applications were the Focused Assessment for Sonography for HIV associated TB (FASH) exam, finding fluid (pericardial effusion, pleural effusion, ascites), qualitative assessment of left ventricular function, and assessment for A-lines/B-lines/consolidation. The following scans met ease of learning criteria: FASH-basic, assessment of LV function, A-lines vs. B-lines, and finding fluid. Finding fluid and assessment of LV function changed diagnosis and management most frequently, greater than 50% of the time for each category.  Discussion/Conclusion: We recommend the following applications as highest yield for inclusion in a POCUS curriculum for IM practitioners within LMICs: finding fluid (pericardial effusion, pleural effusion, ascites) and assessment of gross LV function.